A prospective, multi-centre trial of multi-parametric MRI as a biomarker in anal carcinoma. (March 2020) - Jones, Michael; Hruby, George; Coolens, Catherine; Driscoll, Brandon; Stanwell, Peter; Kumar, Mahesh; Capp, Anne; Sridharan, Swetha; Arm, Jameen; Gallagher, Sarah; Holder, Carl; Oldmeadow, Christopher; et al.
Highlights: Multi-parametric MRI performed during chemo-radiotherapy for anal cancer is predictive of recurrence. DW-MRI parameters appear more prognostic than DCE parameters. Multi-parametric MRI requires further validation as a biomarker in anal cancer. Abstract: Background and purpose: To investigate the role of multi-parametric magnetic resonance imaging (MP-MRI) as a biomarker for squamous cell carcinoma of the anal canal (SCCAC). Materials and methods: From January 2013 to January 2017, 25 patients with non-metastatic SCCAC were enrolled in a multi-centre prospective clinical trial, of whom 20 completed protocol treatment. MP-MRIs, incorporating diffusion weighted magnetic resonance imaging (DW-MRI) and dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) sequences, were performed before (baseline), during the second and fourth weeks of chemo-radiotherapy (CRT), and 8 weeks following treatment completion. Histogram analysis of multi-parametric maps generated maximum, mean, median, minimum, skewness, kurtosis, and standard deviation metrics. Exact logistic regression and ROC AUC analyses were performed for each metric at every timepoint. An elastic net LASSO logistic regression was also performed using all measures at each timepoint. Results: With a median follow up of 17.1 months, 3/20 patients had a local recurrence, and 5/20 had any recurrence. Several apparent diffusion coefficient (ADC) metrics extracted from DW-MRIs correlated with local recurrence and demonstrated excellent discrimination: baseline skewness ( p  = 0.04, ROC AUC 0.90) and standard deviation (SD) ( p  = 0.02, ROC AUC 0.90), week 2 skewness ( p  = 0.02, ROC AUC 0.91) and SD ( p  = 0.01, ROC AUC 0.94), week 4 kurtosis ( p  = 0.01, AUC 0.92) and SD ( p  = 0.01, ROC AUC 0.96). Changes in minimum ADC between baseline and week 2 ( p  = 0.02, ROC AUC 0.94) and baseline and week 4 ( p  = 0.02, ROC AUC 0.94) were prognostic for local recurrence. For prediction of any recurrence, ADC minimum ( p  = 0.02, ROC AUC 0.87) and SD ( p  = 0.01, ROC AUC 0.85) at baseline, and ADC maximum ( p  = 0.03, ROC AUC 0.77) and SD ( p  = 0.02, ROC AUC 0.81) at week 4 were significant. On LASSO logistic regression, ADC minimum and SD at baseline were retained for any recurrence. The only significant finding for DCE-MRI was a correlation of k-trans min at the second follow-up with local recurrence ( p  = 0.05, AUC 0.84). Conclusion: Several ADC parameters at various time points correlate with recurrence suggesting DW-MRI is a potential biomarker for SCCAC.